Nitrogen Metabolism During Hepatectomy and Hyperbaric Oxygenation: Experimental Study - Savilov, P. N. (Obshchai͡a︡ reanimatologii͡a, 2007)
Objective: to examine nitrogen metabolism in the organs of the portal system during liver resection (LR) and hyperbaric oxygenation (HBO).Material and methods: Experiments were conducted on 65 female albino rats. LR was made under ether anesthesia, by removing a portion of the left hepatic lobe with an electric knife, which amounted to 15—20% of the organ’s mass. HBO was performed using medical oxygen at 3 ata for 50 min once daily within the first three days after LR. Lung tissue, gastrointestinal tract (GIT), spleen, and choledochal bile were the subject of the study. The tissue and blood levels of ammonia, glutamine, and urea were measured.Results: LR leads to pathological ammonia accumulation and decreases arterial glutamine consumption in GIT organs. Concurrently, the urea contained in the organs begins to come into portal blood flow, splenic glutamine deficiency develops, and hepatic ammonia-absorptive, glutamine- and urea-excretory functions diminish. Post-LR HBO prevents the accumulation of ammonia in the liver and GIT, restores the ammonia-absorptive, glutamine- and urea-excretory functions of the liver, and stimulates its glutamine and urea accumulation. Concomitantly, under HBO, there is an increase in glutamine entrance from the GIT into blood flow, but there is a decrease in GIT urea excretion and portal venous blood ammonia levels. HBO eliminates arterial hyperammonemia after LR and splenic glutamine deficiency.Conclusion: Hyperbaric oxygen eliminates nitrogen metabolic disturbances in the portal system, regulates compensatory-adaptive ammonia metabolic reactions triggered in the GIT and spleen during LR.